A State of Art Review of Solar/Heat Powered Absorption Cooling Systems Employed in Buildings - Amit Kumar; M K Gupta (AG Volumes, 2022)
Despite the widespread availability of industrial-scale, heat-driven absorption cooling systems, the concept of a solar-powered chillers in air conditioning systems is only getting off the ground. It is not practical to employ absorption chillers for domestic air conditioning since their efficiency is lower than that of compression refrigeration systems, even when operating at smaller scales. In this study, we investigate the viability of using a solar-powered ammonia-water absorption chiller for residential cooling. An air-cooled ammonia-water absorption chiller with a 10 kW capacity that is powered by solar thermal energy has been used to construct a thermodynamic model. In order to gauge how well this cooling system performs at the domestic scale, energy and exergy assessments have been carried out. Most of the exergy is lost in the absorber (63%), next in the generator (13%), and finally in the condenser (11%), as determined by the analysis. As temperatures rise, exergy loss is greatest in the condenser and absorber, drops little in the generator, and is least affected by temperature changes in the evaporator.